Nazi Concentration Camps (aka The Death Camps) (United States, 1945)
Highly graphic images Duration: 01:00:00 This is an official film record of Nazi death camps as photographed by Allied forces advancing into Germany. Although by then the fires in the Third Reich's crematoria had been reduced to smoldering ash, the remaining evidence was so unspeakably horrible that were it not for this film the mind would refuse it. We are made witness to the half-dead prisoners, victims of "medical" experiments, gas chambers, and open mass graves of the camps whose very names have become synonymous with human suffering and degregation. Every frame of the Nazi Concentration Camps is irrefutable testimony to a lesson the world must never be permitted to forget.